The Feminist Fourth Wave : Affective Temporality - Chamberlain, Prudence (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book examines the fourth wave of feminism within the United Kingdom. Focusing on examples of contemporary activism it considers the importance of understanding affect and temporality in relation to surges of feminist activity. Examining the wave's historical use in the feminist movement, the book redefines the symbol in an attempt to overcome difficulties of generations, identities and divisions. The author contends that feminism must develop its own methods for time keeping, in which past activism and future aspirations touch on the present moment. Through this unique temporality, she continues, feminism can make space for affective ties to create intense moments of activism, in which surges of feeling catalyse and sustain mass action. This thought-provoking book, with its exploration of the relationship between feeling, the personal and political, will appeal to students and academics working in the fields of gender studies, feminism and affect studies.
Keywords: Social sciences.; Feminist theory.; Sociology.; Political sociology.; Sex (Psychology).; Gender expression.; Gender identity.; Self.; Identity (Psychology).; elektronické knihy; electronic books